Harbouring the illicit: borderlands and human trafficking in South East Asia - Munro, Peter (Crime, law and social change, 2012)
The unique environment of borderlands in mainland and insular South East Asia has facilitated the growth of human trafficking for sexual and labour exploitation. Organised crime groups have seized upon opportunities offered in these geographic locales to develop this illicit industry. This article examines the dynamics of human trafficking in three diverse border areas in the region: the Cambodian-Thai border; Indonesia-Singapore-Malaysia border; and the Thai-Burmese border. An examination of the unique social and power dynamics of the borderlands and a comparative history of these areas will illustrate how organised crime groups have flourished and engaged in human trafficking to support local border sex industries. This trade preys upon the vulnerable and impoverished living on the fringes of border communities. Weak State institutions, entrenched patronage networks, and distance from central control have made these borderlands ideal for criminals to establish themselves and their illicit activities. These same conditions have made it easy for regional tourists to engage in illicit sex in neighbouring countries with little chance of recrimination.